Enhancement of electromagnetically deposited pristine CdTe film electrode photoelectrochemical characteristics by annealing temperature and cooling rate - Zyoud, Ahed H.; Abdelhadi, Doa' H.; Helal, Mohamed H.S.; Zyoud, Samer H.; Bsharat, Heba; Abu-Alrob, Sohaib M.; Sabli, Nordin; Qamhieh, Naser; Hajamohideen, Abdul Razack; Hilala, Hikmat S. (Elsevier GmbH, 2019)
Photoelectrochemical (PEC) characteristics of CdTe film electrodes, known to have low conversion efficiency when used in their pristine form, can be significantly enhanced by carefully controlling their annealing temperature and cooling rate. Pristine CdTe films were electrodeposited onto FTO/Glass substrates which were used as anodes. To reach films with optimal characteristics, different applied preparation potentials were intentionally examined, namely 1.0, 1.1 and 1.2 V, vs. Ag/AgCl reference electrode (or 1.2, 1.3 and 1.4 V NHE, respectively) where the 1.1 V applied potential showed best PEC characteristics, and was thus followed unless otherwise stated. To study effect of annealing temperature, three temperatures (150, 200 and 250 ºC) were attempted to enhance PEC characteristics of the deposited films. Effect of cooling rate, on PEC performance of pre-annealed films, was also studied using quenching and slow cooling. Films quenched from annealing at all temperatures showed lower PEC performance compared to non-annealed electrode. Film electrodes slowly cooled from 150 or 200 ºC show enhanced PEC performance compared to quenched or non-annealed films. Film slowly cooled from 250 ºC exhibited lower PEC performance than the quenched counterpart. Annealing at 250 ºC lowered PEC for both quenching and slow cooling. As a low band gap semiconductor film electrode, it is recommended to slowly cool CdTe from low annealing temperatures, and to quickly cool them from relatively higher annealing temperature. The annealing temperature and cooling rate effects on CdTe film PEC performance are attributed to their effects on other physical characteristics, namely crystallinity, morphology and chemical composition. The optimal conversion efficiency (6.9%) was observed for film deposited at 1.1 V applied potential when annealed at 200 ºC and slowly cooled to room temperature.